Related variety and regional growth in Spain - Boschma, Ron; Minondo, Asier; Navarro, Mikel (Papers in regional science, 2012)
This paper investigates whether related variety, among other types of spatial externalities, affected regional growth in Spain at the NUTS 3 level during the period 1995–2007. We found evidence that related variety matters for growth across regions, especially when using two new methods that measure revealed relatedness between industries. The first method is based on Porter's cluster classification while the second method uses the proximity index proposed by Hidalgo et al. Our analyses show that Spanish provinces with a wide range of related industries tend to show higher economic growth rates, once we control for other determinants of growth. Este artículo investiga si la variedad relacionada, entre otros tipos de externalidades espaciales, afectó el crecimiento regional en España a nivel NUTS 3 durante el periodo 1995‐2007. Hallamos pruebas de que la variedad relacionada influye en el crecimiento entre regiones, especialmente al utilizar dos métodos nuevos que miden el grado de conexión manifiesto entre industrias. El primer método está basado en la clasificación de conglomerados de Porter, mientras que el segundo método utiliza el índice de proximidad propuesto por Hidalgo et al. Nuestros análisis muestran que las provincias españolas con un amplio rango de industrias relacionadas tienden a mostrar tasas de crecimiento económico más altas, una vez que se logra controlar otros factores determinantes del crecimiento.